Cannabis and Lung Health: Does the Bad Outweigh the Good? - Kaplan, Alan G. (Pulmonary Therapy, 2021)
Cannabis use is growing, with multiple medical ‘indications’ and approval for recreational use in many countries. This article will review some of the respiratory complications to cannabis use, which include lung function changes, lung destruction, increased risk of lung and head and neck cancer, and others. These are mostly related to smoking, and the co-administration of nicotine makes the risks a bit difficult to measure. However, with many reports of EVALI, electronic vaping-associated lung injury, being related to cannabis coadministration, it appears that the safest administration of cannabis, as far as lung health, is orally.